If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3f + -12 = 0 Reorder the terms: -12 + 3f = 0 Solving -12 + 3f = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 3f = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 3f = 0 + 12 3f = 0 + 12 Combine like terms: 0 + 12 = 12 3f = 12 Divide each side by '3'. f = 4 Simplifying f = 4
| 2p(p-3)+4= | | 24+4g= | | 4+35x=28x+7 | | 5t+30= | | -4+3x=-8+13x | | 5x+10=-67-6x | | 20-2x=5-7x | | 2x+8=-27-3x | | (50+x)-(35+x)=15 | | 3x(2k-1)=5x(k-4) | | 8+11x=-42+x | | 24x^2-10x-1= | | 4x+14=4(n+8) | | x+14=4(n+8) | | 4(x-3)+2(x+1)= | | 8h-13=67 | | 4(3t-4)-2=30 | | 7m-11=38 | | Log(x^2+3x+36)=1+log(x-3) | | 14b=2-2 | | 5(2x+6)=-18+2 | | -4x-16=2x-10 | | 0.50x+0.20(9.0-x)=35 | | 12x-24=-4x+88 | | (3-10x)(x+23)=0 | | 12x+24=-4x+-8 | | -2b+4-b-b=2b+4 | | 8x+40=-4x+28 | | cos(0.5x)=0 | | 2*ln(x)+3=0 | | 4[x-2]=3x | | 8(x-12)=4x |